1981
DOI: 10.1113/jphysiol.1981.sp013926
|View full text |Cite
|
Sign up to set email alerts
|

Selective synapse formation during sprouting after partial denervation of the guinea‐pig superior cervical ganglion.

Abstract: SUMMARY1. The synaptic connexions established by sprouting of intact preganglionic sympathetic axons were examined by intracellular recording in vitro and by observing the sympathetic end organ responses to ventral root stimulation in vivo.2. The superior cervical ganglion of the guinea-pig was partially denervated (70-85 %) by crushing the cervical sympathetic trunk at the level of the subclavian artery, leaving the ansa subclavia intact. The intact nerve carried some preganglionic axons arising from each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Because 3 weeks is very early for a complete re‐innervation to occur, it might be possible that synaptic connections occur between the damaged CTN fibers and the cutaneous somatosensory fibers. A similar observation has been made by Maehlen and Nja 17 . They observed synapse formation during sprouting after partial denervation of the guinea‐pig superior cervical ganglion.…”
Section: Discussionsupporting
confidence: 84%
“…Because 3 weeks is very early for a complete re‐innervation to occur, it might be possible that synaptic connections occur between the damaged CTN fibers and the cutaneous somatosensory fibers. A similar observation has been made by Maehlen and Nja 17 . They observed synapse formation during sprouting after partial denervation of the guinea‐pig superior cervical ganglion.…”
Section: Discussionsupporting
confidence: 84%
“…One week after partial denervation of the superior cervical ganglion, there is some degree of sprouting from the remaining preganglionic axons (Maehlen & Nja, 1981), thus it is possible that the increase in e.p.s.p. amplitude observed by us could be due to an increase in the number of synaptic connexions from non-injured axons if the TTX capillary produced some degree of axon damage.…”
Section: Inactivity Effects On Ganglionic Synapsesmentioning
confidence: 99%
“…The fibres forming the ansa subclavia constitute about 17 0 of the fibres in the superior cervical trunk (Maehlen & Nja, 1981) and the rest form the subelavian trunk.…”
Section: Inactivity Effects On Ganglionic Synapsesmentioning
confidence: 99%
“…58, No. 5, May 1986 sidual processess following partial denervation of the superior cervical ganglion in the guninea pig (Maehlen and Nja, 1981). Skeletal muscle in culture has been shown to secrete nerve growth factor (Murphy et al, 1979), and Chamley et al (1973b) suggested that nerve growth factor may account for the specificity of sympathetic innervation of various tissues in culture.…”
Section: Discussionmentioning
confidence: 99%